A Pilot Survey of Hepatitis C Knowledge and Awareness of Novel Treatment Options Engaged with Narcotics Anonymous: How Can Group Therapy Help?. Issue 1 (2nd January 2017) - Gilman, Mark; Littlewood, Richard
ABSTRACT: Chronic hepatitis C virus (HCV) infection is associated with liver disease, including cancer. Novel therapy options make cure possible. People with history of injecting drugs have high HCV prevalence. Groups are effective at promoting health engagement. Thirty-eight people in Narcotics Anonymous completed a pilot survey. All were abstinent but had engaged in risk behavior for HCV. Forty-two percent thought it was difficult to engage for HCV therapy, 65% stated it was hard to access novel treatments, and 97% considered that people in Narcotics Anonymous should find out information about novel HCV therapy. Groups present an important option for promoting engagement in HCV.